A facile one-pot strategy for fabrication of carbon-based microwave absorbers: effects on annealing and paraffin content. Issue 28 (29th June 2017) - Zhang, Yanan; Quan, Bin; Liu, Wei; Liang, Xiaohui; Ji, Guangbin; Du, Youwei
Abstract : The carbon-coated Fe3 O4 and Fe3 C were synthesized at different temperature. The composites obtained at 700 °C possess higher reflection loss and broader effective bandwidth. Abstract : In this work, a one-pot strategy was proposed to synthesize carbon-coated Fe3 O4 and carbon-coated Fe3 C via the pyrolysis of colloidal Fe3 O4 nanocrystals capped with oleic acid (OA) at different calcination temperatures. After exploring the microwave absorption performance of these composites, we found that carbon-coated Fe3 C obtained at 700 °C possesses higher reflection loss (RL) and broader effective bandwidth (RL ≤ −10 dB) at low thickness. So the further investigation of the microwave absorption performance for carbon-capped Fe3 C composites mixed with different mass percentages of paraffin was also carried out. The results demonstrated that the multi-dielectric relaxation process and better impedance matching, especially at low thickness and high frequency, contributed to the preferable microwave absorption greatly.